Cooperative Design, Visualization, and Engineering 9th International Conference, CDVE 2012, Osaka, Japan, September 2-5, 2012. Proceedings - Luo, Yuhua; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 9th International Conference on Cooperative Design, Visualization, and Engineering, CDVE 2012, held in Osaka, Japan, in September 2012. The 36 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers cover the topics of cooperative engineering, basic theories, methods and technologies that support CDVE, cooperative design, visualization and applications.
Keywords: Computer science; Information storage and retrieval systems; Optical pattern recognition; Computer aided design; Computer Science; User Interfaces and Human Computer Interaction; Information Systems Applications (incl. Internet).; Computer-Aided Engineering (CAD, CAE) and Design; Pattern Recognition; Information Storage and Retrieval; Computers and Society